Effects of lightning impulse front time on substation grounding system performance - Muhammad Adnan; Zulkurnain Adul Malek; Nur Syazwani Mohd Din; Muhammad Irfan Jambak; Zainuddin Nawawi; Muhammad Abu Bakar Sidik (Institute of Advanced Engineering and Science, 2020)
The role of the grounding system in the safety of the power system and protection of personnel is obvious during an unexpected short circuit or lightning discharge at the substation. The aim of this work is to analyze the effects of several parameters: lightning impulse front time, soil resistivity and types of grid materials on the grounding system of the Substation. The ground potential rise (GPR), touch voltage and step voltage of a 50 m x 60 m grounding grid buried at a depth of 0.5 m were computed using CDEGS when injected by impulse with different front times. Results show that the shorter the front time of lightning impulse waveform, the higher the value of GPR, touch voltage and step voltage. Meanwhile, when the value of soil resistivity is increased, the value of GPR, touch voltage and step voltage is also increased. Lastly, different types of grid conductor materials give different values of GPR, touch voltage and step voltage. However, it can be said that the differences are too small to be of any significance.